Multi-criteria potential groundwater contamination and human activities: Araras watershed, Brazil - Piga, Fabiola Geovanna; Rodrigues Tao, Nicolas Guerra; Ruggiero, Mayara Herrmann; Marquezola, Darlan de Souza; Oliveira Boina, Welliton Leandro de; Costa, Carlos Wilmer; Lollo, Jose Augusto de [UNESP]; Lorandi, Reinaldo; Melanda, Edson Augusto; Moschini, Luiz Eduardo (Assoc Brasileira Recursos Hidricos-abrh, 2017)
Assessment of groundwater contamination potential using geological, hydrological and hydrogeological attributes, is an efficient mechanism of sub-surface water resources protection and conservation. However, usually this method does not take into consideration the potentially polluting human activities, either in punctual or diffuse sources, or because the relative importance of the attributes are not considered. The paper proposes a multi-criteria approach as a way of solving this gap, reducing subjectivity and considering land use/cover due human actions influence in the process. The study was developed in Araras river watershed (Parana Basin, Brazil) using rock, groundwater, relief, soils, and land use/land cover classification, employing multi-criteria analysis and data of contamination sources. The potential contamination classification showed the predominance (54% of the area) of very high and high potential, especially due to geological environment conditions (exploitation areas and groundwater recharge of the Itarare Aquifer - clastic sedimentary and free flow). The contaminant sources analyzed are located mainly in higher potential contamination areas.
Keywords: Groundwater; Water quality; Water contamination; Multi-criteria analysis